Local limit theorem for coeﬃcients of modiﬁed Borwein’s algorithm, proved by the ratio method - Belovas, Igoris (Lietuvos matematikos rinkinys, 2019)
The paper continues the research of the modiﬁed Borwein method for the evaluation of the Riemann zeta-function. It provides a diﬀerent perspective on the derivation of the local limit theorem for coeﬃcients of the method. The approach is based on the ratio method, proposed by Proschan.